To Explore Potential Inhibitors against Various Enzymatic Targets of Human African Trypanosomiasis - Brahma, Sayandeep; Moitra, Susmita; Bagchi, Soumya Ranjan; Samadder, Asmita; Nandi, Sisir (Combinatorial Chemistry & High Throughput Screening, 2025)
Synthetic drugs currently prescribed for the treatment of Human African Trypanosomiasis (HAT) are non-specific, toxic, demand extended therapeutic regimes and are of varying efficacy. Along with the challenging demographic and socio-economic hurdles, the ever-increasing risk of drug resistance is another major problem to be addressed. Cysteine protease, Heat shock proteins (HSP-90), Trypanothione reductase (TR), Farnesyl diphosphate synthase, Glucose-6-phosphate dehydrogenase, UP-4-galactose epimerase, and Cytidine triphosphate synthetase are potential enzymatic targets for the development of novel inhibitors against HAT which are the main focus of this review. The potential enzymatic targets of Trypanosoma brucei, especially small molecules like cysteine proteases and heat shock proteins are identified as major candidates for the sustenance of the parasite, their proliferation, infection, and spread of the disease. The development of new compounds to combat the disease by thorough ligand modification has been explored in the current review. Extracting these compounds and studying their efficacy, toxicity, and target mechanism extensively, this review has proposed a list of different compounds, including some synthetic and natural compounds along with multi-target inhibitors such as acoziborole, fexinidazole, etc. Potential inhibitors against these enzymatic targets of the T. brucei are important candidates for designing novel therapeutics against HAT. Multi-target inhibitors have also been identified as crucial molecules because of their potential advantage against the development of drug resistance.
Keywords: HAT